Resourcefulness Enactment: The Sensemaking Process Underpinning Resourceful Actions - Fisher, Greg (Entrepreneurship Theory and Practice, 2024)
Prior research highlights how entrepreneurs depend on resourceful actions to overcome constraints in value-creation situations. Yet, most resourcefulness research has examined its external manifestations. To complement this, I examine the cognitive and embodied sensemaking process that underpins resourceful actions. Using an autoethnography of a 1430-mile mountain bike ride across South Africa, I distill a microfoundational sensemaking perspective underpinning resourcefulness, highlighting how actors who confront resource-constrained situations find creative ways to overcome such constraints to move forward in their endeavors. Furthermore, I specify how resourcefulness is impacted by priming, learning, and contagion within a challenging context.